Chiral spin textures in a frustrated kondo lattice model - Munir Shahzad (2017)
Strongly correlated electron systems in which there exists a subtle interplay between spin and charge degrees of freedom give rise to many novel and exotic phases. In these spin-charge coupled systems the itinerant electrons and localized moments affect each other in a self-consistent way. The magnetic interaction between the spins is mediated by the motion of electrons; on the other hand, the transport of these electrons is affected by the underlying spin textures. These systems when arranged on geometrically frustrated lattices stabilize topologically non-trivial chiral conﬁgurations of localized spins that drive unconventional transport phenomenon such as topological or geometrical Hall effect. The Shastry-Sutherland model with appropriate generalization is an excellent framework to study the interplay between charge and spin degrees of freedom on a frustrated geometry. Furthermore, such a model is directly relevant in understanding the transport of rare earth tetraborides – a family of metallic quantum magnets with underlying magnetic Shastry-Sutherland lattice. We investigate Shastry-Sutherland Kondo lattice model (SS-KLM) extensively in different parameter regimes for the ground state phases with unique topological properties using a suite of numerical methods. To reduce ﬁnite-size effects we have implemented two approximate methods truncated polynomial expansion method and traveling cluster approximation – the CPU time for both these methods scales linearly with the system size making it possible to explore larger lattice sizes. We present results for integer quantum Hall effect on Shastry-Sutherland lattice in the presence of longitudinal magnetic ﬁeld. The strong frustration results in decreasing the width of plateaus in Hall conductivity while strong disorder leads to the disappearance of higher plateaus. The rise in temperature smooths out the steps in Hall conductivity making longitudinal conductivity non-zero over the whole range of Fermi energy. We establish the existence of several non-coplanar ground states in the phase diagram of SS-KLM using variational ansatz at T = 0. The previously unknown canted-Flux state is shown to be stabilized over wide range of parametric space in the presence of Dzyaloshinskii-Moriya interaction. Using unbiased Monte Carlo method we show that this complex ground state can be generated dynamically starting from random spin conﬁgurations even at non-zero but a ﬁnite value of temperature at half ﬁlling of itinerant electrons. Moreover, the non-coplanarity of such topologically non-trivial spin textures can be tuned using magnetic ﬁeld. We also demonstrate that non-coplanar ground states are stabilized for n e = 1/4 and 3/4 against thermal ﬂuctuations. Tuning the strength of frustration is shown to drive the system from canted Flux state through different intermediate topologically non-trivial states to topologically trivial anti ferromagnetic ground state. We show that the ground states with different topological character can be stabilized with the help of magnetic ﬁeld. Our results are crucial in understanding the emergence of complex spin textures in metallic magnets and will be important in explaining the magnetic and electronic properties of the rare earth tetraboride family of frustrated metallic magnets.